DEVELOPMENT OF ARTIFICIAL INTELLIGENCE AS A FACTOR OF EDUCATIONAL STRUCTURE TRANSFORMATION IN THE CONTEXT OF THE ENERGY TRANSITION - Elvin Ilyich Muratov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the impact of artificial intelligence development on the transformation of the educational workforce training structure in the context of the global energy transition. The study analyzes the interrelationships between the growth of computational capacity, increasing energy consumption of digital infrastructure, and changing labor market demands. Particular attention is paid to the influence of AI regionalization on the expansion of data centers and the emergence of new requirements for specialist training systems. It is argued that the widespread adoption of artificial intelligence increases demand not only for information technology professionals but also for energy engineers, digital infrastructure operators, and specialists in energy system management.